Genotoxicity of Chlorpyrifos and the Antimutagenic Role of Lettuce Leaves in Male Mice - Abdelaziz, Kamilia Badrakhan; El Makawy, Aida Ibrahim; Elsalam, Ali Zain El-Abidin Abd; Darwish, Ahmed Mohamed (Comunicata Scientiae, 2010)
Chlorpyrifos [O O-diethyl-O-(3 5 6-trichloro-2-pyridyl)-phosphorothioate] is one of the most widely used organophosphate insecticides. Previous studies proved that chlorpyrifos, at different doses, induced genotoxicity. In Egyptian foods, the residual levels of pesticides are often higher than those found in developed country ones. So the aim of this research was to evaluate the genotoxicity of the insecticide chlorpyrifos at doses equal to its maximum residue limit (MRL) in the leafy vegetables, its double and quadruple (0.5, 1 and 2 mg/kg body weight) in somatic and germ cells of male mice. In addition to that, evaluating the role of lettuce leaves as antigenotoxic in reducing the genotoxic effects of chlorpyrifos tested doses when concurrently administrated to these animals. The study was conducted on adult male laboratory mice at three levels: bone marrow cells as a model for mitotic chromosome aberrations, spermatocytes as a model for meiotic chromosomes and sperm count and morphology. The results of the present study indicate that the treatment of male mice with chlorpyrifos by oral gavages for three months induced significant increase in the frequencies of total chromosomal aberrations in both somatic and germ cells in relation to control groups. Results of the sperm analysis showed that chlorpyrifos induced significant decrease in the sperm count when compared to negative control. Furthermore, it induced significant increase in head and tail sperm abnormalities, among which coiled tail was considered the most obvious sperm abnormality induced by chlorpyrifos. At the same time, the present study indicated that lettuce leaves feed concurrently with three doses of chlorpyrifos could not protect cells from damage.